2020
DOI: 10.1128/mbio.03193-19
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Symbiotic Compatibility by Rhizobial Zinc Starvation Machinery

Abstract: Pathogenic bacteria need high-affinity zinc uptake systems to counteract the nutritional immunity exerted by infected hosts. However, our understanding of zinc homeostasis in mutualistic systems such as the rhizobium-legume symbiosis is limited. Here, we show that the conserved high-affinity zinc transporter ZnuABC and accessory transporter proteins (Zip1, Zip2, and c06450) made cumulative contributions to nodulation of the broad-host-range strain Sinorhizobium fredii CCBAU45436. Zur acted as a zinc-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Among the common downregulated genes within G. max nodules induced by rhcV mutants ( Fig. S1 and Tables S3 and S4 ), Glyma.06G052000 encodes a zinc transporter homolog, ZIP ( 51 , 52 ), and znuB encodes an essential component of the high-affinity zinc uptake system of S. fredii ( 53 ). The znuB mutant of SF4 forms many pseudonodules and few normal nodules on G. max cv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the common downregulated genes within G. max nodules induced by rhcV mutants ( Fig. S1 and Tables S3 and S4 ), Glyma.06G052000 encodes a zinc transporter homolog, ZIP ( 51 , 52 ), and znuB encodes an essential component of the high-affinity zinc uptake system of S. fredii ( 53 ). The znuB mutant of SF4 forms many pseudonodules and few normal nodules on G. max cv.…”
Section: Resultsmentioning
confidence: 99%
“…The znuB mutant of SF4 forms many pseudonodules and few normal nodules on G. max cv. C08, and the inactivation of Znu together with accessory zinc uptake proteins leads to downregulation of T3SS genes in the presence of the symbiotic signal genistein ( 53 ). All of these defects can be rescued by supplying replete zinc ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). Notably, MucR1 can also act as a positive regulator required for active transcription of high-affinity transporters for phosphate and zinc ions and the iron-responsive regulator RirA, which are all essential for efficient symbiosis of S. fredii within soybean nodules ( 22 , 35 38 ). The downregulation of rirA in bacteroids of the mucR1 mutant was confirmed in this work but not observed in bacteroids of the P nifH -DGC strain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In small amounts, Zn is needed for all crop plants. Zn application decreases the negative effect of salinity stress (Zhang et al, 2020). This study showed a small increase of Zn concentration in leaves of faba and soybeans (from 14 to 15 mg•kg -1 in faba bean leaves and from 11 to 13 mg•kg -1 in soybean leaves).…”
Section: Discussionmentioning
confidence: 45%